2008
DOI: 10.1186/gb-2008-9-10-r154
|View full text |Cite
|
Sign up to set email alerts
|

Functional architecture of Escherichia coli: new insights provided by a natural decomposition approach

Abstract: network structure

The E. coli transcriptional regulatory network is shown to have a nonpyramidal architecture of independent modules governed by transcription factors, whose responses are integrated by intermodular genes.

AbstractBackground: Previous studies have used different methods in an effort to extract the modular organization of transcriptional regulatory networks. However, these approaches are not natural, as they try to cluster strongly connected genes into a module or locate known pl…
Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(106 citation statements)
references
References 64 publications
6
100
0
Order By: Relevance
“…The carbon metabolism module, for instance, features carbon source specific transcription factors, such as FruR, LldR, GntR1/R2, and the many regulators involved in aromatic compound degradation. The hierarchical and modular structure of the C. glutamicum supercluster reflects the typical topology of bacterial transcriptional regulatory networks (Ma et al, 2004;Resendis-Antonio et al, 2005), and is similar to that of recent E. coli models (Freyre-González et al, 2008;Martínez-Antonio et al, 2008).…”
Section: Reconstruction Of the C Glutamicum Transcriptional Regulatomentioning
confidence: 79%
See 1 more Smart Citation
“…The carbon metabolism module, for instance, features carbon source specific transcription factors, such as FruR, LldR, GntR1/R2, and the many regulators involved in aromatic compound degradation. The hierarchical and modular structure of the C. glutamicum supercluster reflects the typical topology of bacterial transcriptional regulatory networks (Ma et al, 2004;Resendis-Antonio et al, 2005), and is similar to that of recent E. coli models (Freyre-González et al, 2008;Martínez-Antonio et al, 2008).…”
Section: Reconstruction Of the C Glutamicum Transcriptional Regulatomentioning
confidence: 79%
“…In this organism, the synthesis of cAMP by adenylate cyclase is stimulated by a component of the phosphoenolpyruvate:sugar phosphotransferase system, and cAMP levels are coupled to cellular energy levels (Park et al, 2006;Bettenbrock et al, 2007). Crp E. coli has consistently been recognized as global regulator in the transcriptional regulatory network of E. coli, being involved in the regulation of about 400 genes in distinct cellular functionality (Freyre-González et al, 2008;Martínez-Antonio et al, 2008). In this way, Crp E. coli serves as regulatory hub, connecting several functional modules to the network and mediating the cellular response to a high-level signal conveyed by the varying concentrations of cAMP (Kolb et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive network reconstruction revealed a modular and hierarchical structure of regulatory interactions at the transcriptional level (Ma et al, 2004;Resendis-Antonio et al, 2005). Recent results indicated that different organizational levels of the TRN of E. coli are bridged by the presence of positive and negative feedback loops (Freyre-González et al, 2008). The modularity of the TRN accounts for the robustness of the entire system in that way that damage is kept in a certain part of the network (Aderem, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…It is worth noting that each of the highlighted TFs has been described as a global regulator in the transcriptional network of E. coli by at least one of the previously published studies. 15,37,38 This observation suggests that dynamical outliers (which are also identified as structural outliers) are very likely to be global transcription factors. Many distinct features distinguish these factors from the rest of the integrated network: (i) all the factors have a much higher out-degree than in-degree, i.e.…”
Section: Structural and Dynamical Outliers Of The Integrated Network mentioning
confidence: 92%
“…[19][20][21] Consequently, questions have been raised on the generality of the trends. 15 Also of relevance in this context is the link between the structure and dynamics of a network which is most often neglected when studying global properties. Understanding this link becomes important as is demonstrated in the case of network synchronization in cortical network analyses.…”
Section: Introductionmentioning
confidence: 99%